2007
DOI: 10.1097/01.tp.0000251649.01148.f8
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Graft Failure Using the Blood Metabolic Profile of a Liver Recipient

Abstract: In this case report we describe the blood metabolic profile ("metabolomics") by nuclear magnetic resonance (NMR) spectroscopy and principle component analysis (PCA) from a patient who underwent two consecutive liver transplantations. The first graft from a living-related donor failed and was followed by a second successful transplant from a deceased donor. Using quantitative high-resolution H-NMR spectroscopy, 48 endogenous metabolites were analyzed in whole blood samples at baseline and different time points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 18 publications
0
44
0
Order By: Relevance
“…In the field of hepatic transplantation, the widening of indications for liver transplant coupled with the shortage of donors has led to the increased utilization of marginal grafts, which have higher rates of non-function and graft failure [63][64][65]. The need for early diagnosis in these settings is becoming more apparent.…”
Section: Transplantationmentioning
confidence: 97%
“…In the field of hepatic transplantation, the widening of indications for liver transplant coupled with the shortage of donors has led to the increased utilization of marginal grafts, which have higher rates of non-function and graft failure [63][64][65]. The need for early diagnosis in these settings is becoming more apparent.…”
Section: Transplantationmentioning
confidence: 97%
“…This particular characteristic of NMR spectra helps reduce the problem of spectral (or chromatographic) redundancy as it is unlikely that any two compounds will have identical numbers of peaks with identical chemical shifts, identical intensities, identical spin couplings or identical peak shapes. Likewise, with higher magnetic fields (>600 MHz) the chemical shift separation among different peaks and different compounds is often good enough to allow the unambiguous identification of up to 100 compounds at a time, through simple curve fitting [11,34,45].…”
Section: Targeted or Quantitative Metabolic Profilingmentioning
confidence: 99%
“…In targeted metabolic profiling, the compounds in a given bio-fluid or tissue extract are actually identified and quantified by comparing the bio-fluid spectrum of interest to a library of reference spectra of pure compounds [11,34,44,45]. The basic assumption in targeted profiling is that the spectra obtained for the bio-fluid (which is a mixture of metabolites) is the sum of individual spectra for each of the pure metabolites in the mixture (see Fig 30.4).…”
Section: Targeted or Quantitative Metabolic Profilingmentioning
confidence: 99%
“…They proposed six metabolites as potential markers of nonfunctional liver. They concluded that lactate, uric acid, glutamine, total fatty acids, methionine and citrate had significant quantitative differences between the successful and unsuccessful transplantation [12]. Although there have been a great number of studies about the causes of unsuccessful transplantations, there are still no validated biomarkers that could accurately predict graft function.…”
Section: Introductionmentioning
confidence: 96%